2021
DOI: 10.1097/aog.0000000000004497
|View full text |Cite
|
Sign up to set email alerts
|

Abortion Access for Incarcerated People

Abstract: OBJECTIVE: To understand abortion incidence among incarcerated people and the relation to prison and jail pregnancy policies. METHODS: We collected abortion numbers and policy data from convenience sample of 22 state prison systems, all Federal Bureau of Prisons sites, and six county jails that voluntarily reported monthly, aggregate pregnancy outcomes for 12 months in 2016–2017. Sites also completed a baseline survey of institution characteristics and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
27
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(27 citation statements)
references
References 19 publications
0
27
0
Order By: Relevance
“…The US-based Pregnancy in Prison project found that only 1% of pregnancies among federally incarcerated women resulted in abortion. 8 A 2021 study of pregnancy outcomes in state prisons and county jails found an abortion rate of 4.2%, 9 while yet another study among county jails found a rate of 15%. 10 In 2019 the CDC found that 16% of pregnancies that did not miscarry ended in abortion among the general US population 11 - a rate vastly higher than what was observed in the federal prisons.…”
Section: Abortion Rate In Prisonsmentioning
confidence: 99%
“…The US-based Pregnancy in Prison project found that only 1% of pregnancies among federally incarcerated women resulted in abortion. 8 A 2021 study of pregnancy outcomes in state prisons and county jails found an abortion rate of 4.2%, 9 while yet another study among county jails found a rate of 15%. 10 In 2019 the CDC found that 16% of pregnancies that did not miscarry ended in abortion among the general US population 11 - a rate vastly higher than what was observed in the federal prisons.…”
Section: Abortion Rate In Prisonsmentioning
confidence: 99%
“…In 34 studies, the population was currently incarcerated [ 2 , 4 , 5 , 12 31 , 33 , 35 , 41 , 43 , 44 , 45 48 , 50 ]. Two studies included formerly incarcerated people [ 32 , 34 ]; four studies included prison staff [ 37 40 ]; one included people under community supervision [ 49 ]; and one included people involved in the criminal legal system broadly defined [ 36 ]. Additionally, Erickson et al, (2017) [ 51 ] focused on sex workers; we included this study because 27% of respondents reported being formerly incarcerated, and sex work is criminalized in Uganda, the site of the study.…”
Section: Resultsmentioning
confidence: 99%
“…One study [ 35 ] analyzed distances between abortion clinics and prisons among 75 state prisons and 20 federal prisons. Twenty-four studies used quantitative methods, including 14 surveys [ 5 , 14 , 15 , 17 19 , 22 , 24 26 , 29 , 30 , 37 , 45 ]; four secondary data analyses [ 21 , 31 , 40 , 48 ]; one randomized control trial [ 13 ]; four prospective studies [ 4 , 40 , 41 , 43 ] and one study using geo-localization [ 35 ]. Our results also included 14 qualitative studies [ 2 , 12 , 20 , 23 , 28 , 32 , 34 , 38 , 39 , 46 , 47 , 49 51 ], four cross-sectional studies [ 18 , 36 , 42 , 44 ], and one mixed-methods study [ 33 ].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations